Language Creativity in Presenting Hindu Religion Material - Jatiyasa, I Wayan; Juliantari, Ni Kadek (Jayapangus Press, 2024)
Teachers are required to be creative in packaging learning activities in various ways. One of the creativity carried out by prospective teaching students is modifying familiar songs into songs containing learning material about Hindu religion. Therefore, it is important to conduct this research to describe language creativity in presenting Hindu religious material and the obstacles faced in modifying songs. Creativity in presenting material is very important in order to achieve effective communication in learning activities. This research is classified as qualitative research with an empirical approach. This research was carried out by collecting a number of songs containing Hindu Religious Education material developed by students of the Hindu Religious Education Study Program, College of Teacher Training and Education (STKIP) Agama Hindu Amlapura in classroom management practices and interviewing students regarding the difficulties or obstacles experienced when being creative in modifying songs so that they contain Hindu religious material. The results of this research show that there are several songs that students tend to create and modify in classroom management, namely children's songs whose rhythms are very familiar, such as the songs Balonku, Pelangi-Pelangi, Lihat kebunku, Naik Becak, Satu-Satu Aku sayang Ibu. From the rhythm of these songs, they were modified into songs containing Hindu religious material, namely Panca Yadnya, Panca Sraddha, Tri Pramana, Three Basic Frameworks of Hindu Religion, Tri Kaya Parisudha, Holy Books and Holy Places Hindu religion. When carrying out this creativity, students also experience various difficulties or obstacles, such as using diction, adjusting rhythm, packaging material, and limitations for complex material.